No difference in cumulative live birth rates between cleavage versus blastocyst transfer in patients with four or fewer zygotes: results from a retrospective study. Issue 3 (22nd July 2022) - De Croo, I; Colman, R; De Sutter, P; Stoop, D; Tilleman, K
Abstract: STUDY QUESTION: Is the cumulative live birth rate (CLBR) per oocyte collection cycle (OCC) comparable after cleavage-stage or blastocyst-stage transfer in combination with supernumerary blastocyst vitrification on Day 5 (D5) in patients with four or fewer zygotes on Day 1? SUMMARY ANSWER: The CLBR in a fresh blastocyst-transfer or cleavage-stage transfer policy followed by vitrification on D5 is comparable in patients with four or fewer zygotes. WHAT IS KNOWN ALREADY: Blastocyst transfer enhances the self-selection of the embryo and shortens the time to pregnancy in patients with normal or high ovarian response. Whether these advantages are also present in patients with a low ovarian response and/or a limited number of available zygotes is a continuous debate. STUDY DESIGN, SIZE, DURATION: This was a retrospective, observational cohort study of 2359 consecutive OCCs between January 2014 and December 2018. According to a shift in transfer policy in our center, 571 OCCs had been scheduled for a fresh transfer on Day 3 (D3) and 1788 on D5. The D5 group was matched to the D3 group by propensity score (PS) matching according to multiple maternal baseline covariates. After PS matching, there were 571 OCCs in each group. PARTICIPANTS/MATERIALS, SETTING, METHODS: OCCs scheduled for a D3 transfer (n = 571) or for a D5 transfer (n = 1788) were matched by PS matching in a 1:1 ratio accounting for potential confounding factors associated with CLBR. The model included patient characteristics, such as maternal age and cycle rank, as well as treatment characteristics such as GnRH analog regimen and ovarian response. Embryological variables included the number of zygotes and the number of 6- to 7- and 8-cell embryos on D3. The delivery outcomes of the fresh treatment cycle and the consecutive vitrified-warmed embryo transfers were analyzed up to the first live birth. The primary endpoint of this study was CLBR per OCC. Secondary outcomes were live birth rate per fresh transfer and embryo implantation rate per transferred embryo. MAIN RESULTS AND THE ROLE OF CHANCE: The CLBR per OCC was comparable between the D5 and D3 groups (16.8% versus 17.7%, respectively, P = 0.600). Live birth rates per OCC did not differ between a cleavage-stage transfer and blastocyst-stage transfer policy (15.2% versus 12.4%, respectively, P = 0.160). In the D5 group, 201 cycles did not result in a blastocyst to perform an embryo transfer or cryopreservation; in the D3 group, only 59 cycles did not have an embryo transfer because of poor embryo quality (35.2% versus 10.3%, respectively; P < 0.001). A significantly higher number of fresh double embryo transfers were performed in the D3 group compared to D5 (23.8% versus 7.0%, respectively, P < 0.001). LIMITATIONS, REASONS FOR CAUTION: Although adjusted for important confounders in the PS matching, BMI and embryo quality of the transferred embryo(s) were not taken into account. This study is limited by its retrospective design and is a single-center study, which may limit the generalizability of our findings. WIDER IMPLICATIONS OF THE FINDINGS: The CLBR in a fresh blastocyst-transfer or cleavage-stage transfer policy followed by vitrification on D5 is comparable. A fresh embryo transfer on D3 can still be considered in patients with a poor ovarian response and/or limited number of zygotes when combined with blastocyst vitrification without impacting the overall CLBR of the cycle. STUDY FUNDING/COMPETING INTEREST(S): No external funding was obtained for this study. There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: This retrospective study was approved by the local ethical committee at Ghent University Hospital (B 670201731234).